FUNGSI PENDIDIKAN ISLAM DALAM KEHIDUPAN MANUSIA - Muhammad Yahdi (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
The Almighty God blesses human with ‘fitrah’ (basic competence) to play their role as the most noble creature. Human can observe their nature and it may lead them to perfection. Misbehaved human are those who do not understand the meaning of ‘fitrah’ correctly. Fitrah controls all human activities and behaviours in the community. This is the reason why human should do something advantageous and be advantageous to others.